(untitled) (Constructionism Conference Proceedings, 2025)
Contemporary society requires urgent changes in traditional education to engage students and foster innovation, critical thinking, and ethical use of digital technologies. Maker Education, based on Seymour Papert’s constructionism, emphasizes knowledge construction through the production of meaningful objects, while promoting the use of technology. However, challenges such as teacher training, curriculum integration, and activities incorporating students’ realities and interests hinder its implementation. This article presents a field study conducted in a public school in São Paulo, Brazil, involving a sixth-grade class and six teachers from different disciplines. Initially designed to teach mathematical concepts through an interactive game related to soccer, the project evolved into an interdisciplinary learning experience when a student raised concerns about urban inequality linked to a nearby soccer stadium construction. This shift enabled students to engage critically with real-world issues while aligning with pedagogical objectives as proposed by Paulo Freire. The study shows how integrating Maker Education into the curriculum enhances interdisciplinary and contextualized learning, empowering students to actively understand and address social challenges.